Hydrochar Generation from Hydrothermal Carbonization of Organic Wastes - P. Kantakanit (2018)
© Published under licence by IOP Publishing Ltd. Organic wastes from leftover food contributes to a large fraction of municipal solid waste. Because of its high moisture content, it is not suitable to be processed in a conventional way of burning. This study is interested in the possibility to apply hydrothermal carbonization (HTC) process to organic wastes. The objective was to study characteristics of HTC products as a function of temperature and residence time (180-250°C and 1-6 h). Samples of organic waste from discarded foods were processed in a HTC reactor. From the result of hydrochar analysis, it was shown that highest heating value and energy densification were 30 MJ/kg and 1.80 respectively, at 250°C and 3 h. The aqueous solution was found to contain minor concentration of fertiliser nutrients. These products may be used as fuel and chemicals as well as applications in agriculture. It was confirmed that valuable products can be generated from organic waste using hydrothermal carbonization.